Effect of sleep deprivation and NREM sleep stage on physiological brain pulsations - Helakari, Heta; Järvelä, Matti; Väyrynen, Tommi; Tuunanen, Johanna; Piispala, Johanna; Kallio, Mika; Ebrahimi, Seyed Mohsen; Poltojainen, Valter; Kananen, Janne; Elabasy, Ahmed; Huotari, Niko; Raitamaa, Lauri; et al. (Frontiers in Neuroscience, 2023)
Sleep increases brain fluid transport and the power of pulsations driving the fluids. We investigated how sleep deprivation or electrophysiologically different stages of non-rapid-eye-movement (NREM) sleep affect the human brain pulsations. Fast functional magnetic resonance imaging (fMRI) was performed in healthy subjects (n=23) with synchronous electroencephalography (EEG), that was used to verify arousal states (awake, N1 and N2 sleep). Cardiorespiratory rates were verified with physiological monitoring. Spectral power analysis assessed the strength, and spectral entropy assessed the stability of the pulsations. In N1 sleep, the power of vasomotor (VLF < 0.1 Hz), but not cardiorespiratory pulsations, intensified after sleep deprived vs. non-sleep deprived subjects. The power of all three pulsations increased as a function of arousal state (N2>N1>awake) encompassing brain tissue in both sleep stages, but extra-axial CSF spaces only in N2 sleep. Spectral entropy of full band and respiratory pulsations decreased most in N2 sleep stage, while cardiac spectral entropy increased in ventricles. In summary, the sleep deprivation and sleep depth, both increase the power and harmonize the spectral content of human brain pulsations.